ANALYSIS OF THE LEGAL RESPONSIBILITY OF THE NOTARY FOR THE ISSUANCE OF COVERNOTE ON BANKING CREDIT - Andi Melantik Rompegading (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2020)
The covernote is a letter explaining that there is a process that is still ongoing in processing deeds that still need to be completed. This usually happens in credit agreements which require a certificate as a collateral object . There is no phrase that determines that the covernote is within the authority of the notary. The Cover Note itself is not an authentic deed, because it does not comply with the provisions of Article 1868 of the Civil Code. The aim of this research is to analyze the notary's responsibility for issuing covernotes on banking credit. The method used is normative research with an open legislative and conceptual approach. The notary's responsibility in issuing a covernote for disbursement of banking credit is that the covernote must be complete, transparent, and informative and accompanied by attachments that support the contents of the covernote itself. And if there is a discrepancy between the statement in the covernote and the field, the notary can be prosecuted criminally, namely participation or civil liability in the form of compensation to the bank.